1996
DOI: 10.1002/apmc.1996.052360109
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental properties of fluoropolyether‐based resins and related coatings

Abstract: New fluoropolyether polyolic resins are presented suitable to be cured with conventional hardeners as polyisocyanates or melamines. These resins are prepared by addition of fluoropolyether macrodiols (Fomblin@ ZDOLTX) of various molecular weights to isophorone diisocyanate (IPDI) to give oligomeric NCO-terminated prepolymers. The final hydroxy functionality is obtained by the reaction of those prepolymers with trimethylolpropane (TMP). The viscosity of the resins is measured at various concentrations (weight f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…This behavior is very typical of block copolymers based on PFPE [4][5][6][7] and can be explained by the extremely low solubility parameter (about 11 MPa 0.5 ) of perfluorinated polyethers. [11] It is evident that the polymer has one glassy phase at ambient temperature, and therefore during the room temperature curing the reactive functions of the polyurethane are supposed to freeze and loose progressively their molecular mobility.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This behavior is very typical of block copolymers based on PFPE [4][5][6][7] and can be explained by the extremely low solubility parameter (about 11 MPa 0.5 ) of perfluorinated polyethers. [11] It is evident that the polymer has one glassy phase at ambient temperature, and therefore during the room temperature curing the reactive functions of the polyurethane are supposed to freeze and loose progressively their molecular mobility.…”
Section: Resultsmentioning
confidence: 95%
“…[4][5][6][7] Some kinetic studies were also reported dealing with the reaction of perfluoropolyether (PFPE) macrodiols with cycloaliphatic and aromatic diisocyanates [8] to give linear prepolymers: while uncatalyzed reactions resulted very slow, PFPE alcohols are sensitive to the effect of catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…From an examination of Table 3 data, it appears that all the coatings are amorphous and biphasic (two different Tg indicated) due to the thermodynamic segregation of fluoroether and urethane parts; such a phenomenology is well known and already observed and reported for solventborne fluoroether polyurethane coatings [2]. The efficiency of crosslinking was investigated by MEK test.…”
Section: Thermal Transitions and Surface Propertiesmentioning
confidence: 96%
“…Their surface properties like hydrophobicity and cleanability can be improved by introducing low surface tension fluorinated monomers or macromers, like in case of fluorinated polyether containing polyurethanes [2][3][4]. In these products it was observed that water permeability, barrier properties and durability are largely affected by phase segregation phenomena involving the apolar fluoroether segments and polar urethane moieties [2].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation